Multiple criteria decision-making for bio-energy projects assisted by GIS: current applications and perspectives - Rozakis S.; Casalegno S.; Gilliot J.-M. (Comprehensive economic and spatial bio-energy modelling, 2002)
Models related to the different stages of bio-electricity production form an integrated model for the evaluation of bio-electricity projects. A variable number of agents is involved in this vertically operating activity. The integrated model can be defined as a Spatial Decision Support System (SDDS) when assisted by a G.I.S. A spatial database containing expert knowledge and environ-mental models interact with an economic model. This latter is built based on the hypotheses that farmers supply biomass to a competitive market and industry breaks even. As bio-energy chains are currently not viable, the government subsidises this activity in the form of allocated tax exemptions. These subsidies are rendered justifiable to the taxpayers as necessary expenses incurred to reduce the negative effects of fossil fuel energy consumption to the environment. In order to assist real life complex decision problems, a multicriteria module enables selection among alternative solutions with respect to different criteria. A case study involving bio-electricity project decision-making for the plain of Thessally, Greece, illustrates this methodology. Plant capacity, siting and technology selection are determined simultaneously by the model. The cultivation of cynara and miscanthus was assessed on arid and irrigated land. Land resource is a constraining factor to the System, its availability being subject to increasing opportunity costs. Compromise solutions based on economic, environmental and social criteria are provided by the SDSS with costs that varied between 0.06 and 0.13 €/kWh at biomass marginal costs from 30 to 65 €/t. A discussion follows on the contribution of such a tool to the development of bio-energy. This requires adaptation of the multiple criteria module to the needs of interactive decision-making, and the development of a tool fully operational in a GIS-software environment. Ideally, this tool should be available to the bio-energy community through the use of Internet resources containing full objective information so as to feed public debate on this issue. In this way, pre-feasibility studies of biomass projects to be undertaken in the medium term in Europe could be adequately supported on a regional basis. By fully exploiting G.I.S. technological capacities, public decisions makers will be able to evaluate and appropriately adjust funding and regulation policies.
Seminar on Comprehensive Economic and Spatial Bio-Energy Modelling, 2001/06/07-08, Grignon (France)